Burden of disease from inadequate water, sanitation and hygiene in low‐ and middle‐income settings: a retrospective analysis of data from 145 countries. Issue 8 (30th April 2014) - Prüss‐Ustün, Annette; Bartram, Jamie; Clasen, Thomas; Colford, John M.; Cumming, Oliver; Curtis, Valerie; Bonjour, Sophie; Dangour, Alan D.; De France, Jennifer; Fewtrell, Lorna; Freeman, Matthew C.; Gordon, Bruce; et al.
Abstract Objective To estimate the burden of diarrhoeal diseases from exposure to inadequate water, sanitation and hand hygiene in low‐ and middle‐income settings and provide an overview of the impact on other diseases. Methods For estimating the impact of water, sanitation and hygiene on diarrhoea, we selected exposure levels with both sufficient global exposure data and a matching exposure‐risk relationship. Global exposure data were estimated for the year 2012, and risk estimates were taken from the most recent systematic analyses. We estimated attributable deaths and disability‐adjusted life years (DALYs) by country, age and sex for inadequate water, sanitation and hand hygiene separately, and as a cluster of risk factors. Uncertainty estimates were computed on the basis of uncertainty surrounding exposure estimates and relative risks. Results In 2012, 502 000 diarrhoea deaths were estimated to be caused by inadequate drinking water and 280 000 deaths by inadequate sanitation. The most likely estimate of disease burden from inadequate hand hygiene amounts to 297 000 deaths. In total, 842 000 diarrhoea deaths are estimated to be caused by this cluster of risk factors, which amounts to 1.5% of the total disease burden and 58% of diarrhoeal diseases. In children under 5 years old, 361 000 deaths could be prevented, representing 5.5% of deaths in that age group. Conclusions This estimate confirms the importance of improving water and sanitation in low‐ and middle‐income settings for the prevention of diarrhoeal disease burden. It also underscores the need for better data on exposure and risk reductions that can be achieved with provision of reliable piped water, community sewage with treatment and hand hygiene.